2019
DOI: 10.1002/jsfa.9761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar application with sodium selenate on selenium biofortification and fruit quality maintenance of ‘Starking Delicious’ apple during storage

Abstract: BACKGROUND Selenium (Se) is an essential micronutrient due to its anticarsinogenic properties and positive influence on human immune system. Fortification of some fruits based on their rates of consumption and availability all year round appears to be an effective way to supplement Se in the human diet. In this study the possibility of augmenting Se content in ‘Starking Delicious’ apple fruit during two growing seasons was investigated. In 2016, the impact of 0, 0.5, 1 and 1.5 mg Se L−1 by foliar application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…It seemed that the mechanical strength of plant tissues due to Si was generally because of amorphous solid Si deposition on cell wall layers 67 . On the other hand, the effect of Se on fruit firmness could be assigned to the prevention of different oxidative reactions in different fruits 68 .…”
Section: Discussionmentioning
confidence: 99%
“…It seemed that the mechanical strength of plant tissues due to Si was generally because of amorphous solid Si deposition on cell wall layers 67 . On the other hand, the effect of Se on fruit firmness could be assigned to the prevention of different oxidative reactions in different fruits 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Selenium (Se) has been considered as a beneficial element for crop production which plays an important role in physio-biochemical processes [22,23]. Although higher plants do not require Se for their growth and development [24,25], supplementation of Se at lower dosages not only protects plants from ROS induced oxidative damage by activating the antioxidative mechanisms [22], but also improves the Se content in the edible parts of the crop plants [26]. Some studies have shown that Se is an essential element for human and animal, which plays some beneficial roles in higher plants.…”
Section: Of 27mentioning
confidence: 99%
“…Selenium has been reported to improve yield in low dosage (Narváez-Ortiz et al, 2018;Rady et al, 2020) and act as antioxidant when plant capacity increases to resist oxidative stress caused by ROS under stress conditions. This effect is due to a decrease in lipid peroxidation, H2O2, and superoxide radicals, as well as an increase in peroxidase enzymes and polyphenol oxidase (Boldrin et al, 2016;Babalar et al, 2019).…”
Section: Yieldmentioning
confidence: 99%